ASSOCIATIVISMO FEMININO, BAILES DE DEBUTANTES E MEMÓRIAS: HISTÓRIA DAS MULHERES E O GRÊMIO FLORES DA PRIMAVERA EM IRATI-PR (1954-1978) - ANTOSZCZYSZYN, LUCAS (2022)
This dissertation presents stories and memories of women from and in Grêmio Flores da Primavera, in Irati - Paraná, from the perspectives of Gender Relations and Women's History. The temporal cut is established during the years 1954 - 1978, as it presents itself as a viable cut to understand society, women and gender relations in their local dimensions. To this end, it was necessary to reflect on the Iratian society, which underwent transformations arising from the urbanization and industrialization process between the 1950s and 1960s (the "golden years" of Brazilian cultural production), which enabled the rise of a significant group to the middle class, due to the increase in purchasing power, but much more due to the possession of means of production, skills and organization. In this way, these people started to form selective groups and enjoy these formal spaces of sociability, such as clubs and associations with a ludic and recreational content, demarcating a social elite, composed of influential people in the sphere of formal sociability in the urban environment. This phenomenon is analyzed by understanding the symbolic schemes that delimit the differences, the meanings, as proposed by Pierre Bourdieu (1998). In Irati in the 1950s, the Clube do Comércio could add men from this category, while women could join the Grêmio Flores da Primavera. A separation was identified between the clubs, aimed at the male association, and the guilds, towards the female association, due to the presence of discourses that, based on biological differences, established cultural, social and political differences between them. Founded in 1921, Grêmio Flores da Primavera was one of the spaces of formal sociability frequented by women of the social elite and had devices aimed at the construction and maintenance of femininity. From the 1950s to the 1980s, in this guild, a tradition was built, the organization of debutante balls, events that are hallmarks of the urbanization period and that reflect in conservative discourses regarding the role of women in society. After the 1980s, debutante balls became less and less frequent, as was the activity of the Grêmio Flores da Primavera membership. By enjoying these masculinized and feminized spaces (the men's club and the women's guild), the social elite produced and was incorporated by symbolic capital, departing from forged strategies to achieve their goals, whether recognition among peers inside the clubs (the members of the club and members of the guild, which includes their respective directors) while the ''equally sociable'', were the recognition before the Iratiense society. With regard to the women's guild, it was possible to conclude historiographical analyzes of documents left by this organization, by its participants and by the debutantes, which constitute themselves as historical sources. Several documental corpus were analyzed, such as minutes, official letters, correspondence, columns in periodicals, mass booklets, dance carnets, memories obtained orally. Thus, traces of how these women's performance, experience and organization would be in that context of Iratian society, allowing an understanding under the domain of the symbolic schemes that such historical agents were involved, which reinforce the differences built between the genders. To support these discussions, we took as parameters the methodological theoretical contributions of Joan Scott, Pierre Bourdieu, Michel Foucault, Michel de Certeau, Michelle Perrot, Roger Chartier, Maurice Halbwachs, Michael Pollak, among many other researchers from the most diverse areas of knowledge.